(untitled) (Journal of the College of Basic Education, 2022)
Four samples of commercial brand of ready powdered Saccharomyces cerevisiae were collected from local market (Town and Angel/ China , Saf/ France and Pakmaya/ Turkey) for detection their ability to produce killer toxin against eleven isolates of microorganisms: Lactobacillus acidophilus , Pseudomonas aeruginosa, Pseudomonas fluorescens, Staphylococcus aureus , Serratia marcescens , Cladosporium spp., Fusarium spp., Aspergillus spp. and three isolates of Candida albicans , as well as S. cerevisiae isolates. Results showed that Angel yeast was the best one for production of killer toxin ,no production of killer toxin was observed by other isolates of S. cerevisiae. Also some optimum conditions for production of killer toxin was determined and the results showed that cultivation of yeast in glucose yeast extract peptone broth(GYEPB),adjusted at pH 5 and incubated at 25°C for 48 hours was the best to produce it .